Exploring the concurrence of phase transition and grain growth in nanostructured alloy. (1st October 2016) - Huang, Linke; Lin, Weitong; Lin, Bo; Liu, Feng
Abstract: In nanostructured alloys, the concurrence of (solid-state) grain growth and phase transition is ubiquitously observed; however, due to the lack of kinetic evidences, the underlying physics of concurrence remains scarcely understood. In this study, for nanostructured Fe alloy as a model system, macro- and micro-scale characterizations for the concurrence were carried out using in situ X-ray diffraction and in situ high-resolution transmission electron microscopy (HRTEM). Macroscopically, the grain growth occurs and ceases before the end of phase transition, and microscopically, the concurrence of grain boundary (GB) and phase boundary (PB) migrations was certified as well. These experimental results, together with the ex situ HRTEM and molecular dynamics simulation, uncovered the interaction between GB and PB migrations, i.e., both velocity and direction of the PB migration are influenced when the PB interacts with the GB. On this basis, the concurrence was utilized to produce a new kind of heterogeneous and hierarchical microstructure (i.e., dual-phase bimodal nanostructure). The present findings, yield a deep understanding of the phase transition in nanostructured alloys, and further, demonstrate the potential usage of concurrence in manipulating the nanostructures for the development of nanostructured alloys. Graphical abstract: